Thermoelastic effect in compacted steel wire ropes under uniaxial loading. Issue 4 (8th August 2021) - Szade, Piotr; Szot, Mariusz; Kubiś, Bogusław
ABSTRACT: The aim of the research presented in this work was to verify the occurrence of the thermoelastic effect in compacted steel wire ropes for future research applications and TSA methods. It was examined using a Testo 890 thermal camera during tests consisting of 10 cycles of loading of rope samples to levels under the yield stress, performed on a tensile strength machine. Average measured changes of temperature caused by a 1000 MPa change of stress were 0.8 K during loading and 1.0 K during unloading. It was found that rapid unloading caused temperature changes that were closer to the theoretical values calculated for an isotropic body and adiabatic conditions. Probable reasons for those differences were investigated. Furthermore, temperatures of samples recorded after each cycle of loading were analysed. Heating of samples during cycles of elastic elongation was observed, pointing to exothermal processes taking place in the internal structure of the ropes. Application of IR cameras to detect dynamic load changes using the thermoelastic effect in steel wire ropes was proposed and evaluated. Usage of described novelty method in inspection of steel wire ropes during the operation was discussed.